2012
DOI: 10.1103/physrevlett.108.037802
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Pair Correlations and Structure Factors of Confined Hard-Sphere Fluids: An Experimental and Theoretical Study

Abstract: We address the fundamental question: how are pair correlations and structure factors of hard-sphere fluids affected by confinement between hard planar walls at close distance? For this purpose, we combine x-ray scattering from colloid-filled nanofluidic channel arrays and first-principles inhomogeneous liquidstate theory within the anisotropic Percus-Yevick approximation. The experimental and theoretical data are in remarkable agreement at the pair-correlation level, providing the first quantitative experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 28 publications
5
67
1
Order By: Relevance
“…Recently, however, methods have become available thanks to a combination of classic liquid-state theory and modern computational power that yields accurate results on practical timescales. We develop here a description of the soft structure between polarizable walls derived from a single theoretical framework, with minimal assumptions, matching the reliability of a Monte Carlo simulation (21)(22)(23), and agreeing with experimental observations (24). This description provides a practical understanding of electrostatic correlations in charged fluids and predictability in experiments.…”
mentioning
confidence: 65%
“…Recently, however, methods have become available thanks to a combination of classic liquid-state theory and modern computational power that yields accurate results on practical timescales. We develop here a description of the soft structure between polarizable walls derived from a single theoretical framework, with minimal assumptions, matching the reliability of a Monte Carlo simulation (21)(22)(23), and agreeing with experimental observations (24). This description provides a practical understanding of electrostatic correlations in charged fluids and predictability in experiments.…”
mentioning
confidence: 65%
“…For these large packing fractions the dynamics tends to become very slow. Such a dramatic slowdown of dynamics usually is termed glassy dynamics and its relation to structure is the subject of intensive research [16,19,75,[80][81][82][83][84][85][86]. Advanced theories that deal with glassy dynamics, e.g., mode coupling theory [81,83], its generalization [86], and similar approaches [80,82,85], rely on the knowledge of the structure of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Examples range from liquid supply, adhesion to lubrication, friction in narrow channels as well as in biological systems. Confinement effects for densely-packed liquids have been investigated in slit geometry mainly by computer simulations [104,105] and experiments [106,107] focusing on the regime of moderate confinement with slit widths of several particle diameters or larger. These studies revealed the existence of an oscillatory density profile close to the wall [106].…”
Section: Confined Liquidsmentioning
confidence: 99%